Curriculum Theories Adopted in the Development of the Islamic Religious Education Curriculum at MIS Fauzan Al Islamiyah - Nasution, Rabitha Rahmi; Winata, Aguslim M (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the curriculum theories adopted in the development of the Islamic Religious Education (PAI) curriculum at MIS Fauzan Al Islamiyah and evaluate their relevance to the objectives of Islamic education. This study uses a qualitative approach with a case study design, where data are collected through in-depth interviews with the madrasah principal, PAI teachers, and other relevant parties, supported by direct observation of the learning process and a review of curriculum documents such as syllabi, lesson plans, and madrasah archives. The results show that the development of the PAI curriculum at MIS Fauzan Al Islamiyah adopts a constructivist approach that emphasizes student activeness in building knowledge through discussion, group work, and problem solving. Learning is systematically designed through introductory, core, and closing stages by involving small and large groups to hone critical and creative thinking skills, and connect the subject matter with students' real experiences. This curriculum successfully integrates cognitive, affective, and psychomotor dimensions that align with Islamic spiritual and social values. However, several challenges were identified, such as teachers' limited understanding of the curriculum framework, limited supporting resources, high administrative burdens, and difficulties in assessing students' affective aspects. This study recommends improving teacher competency, providing supporting facilities, and strengthening collaboration between madrasas, parents, and policymakers to optimize the implementation of the Islamic Religious Education curriculum.